An exploration of the ceramic technology of a northern Chilean community, evidence from the Caleta Vitor Archaeological Complex. (August 2022) - Morton, Catherine A.; Roberts, Amy; Santoro, Calogero M.; Popelka-Filcoff, Rachel S.; Zhao, Jing
Highlights: Northern Chilean earthenware paste traditions continue over 2500 years. Andean polities did not impact this sphere of material culture production. Contribute to a local northern Chilean narrative. Abstract: This paper discusses the results of statistical analyses of the domestic ceramic assemblage from the Caleta Vitor Archaeological Complex, northern Chile, a collection that spans 2500 years. Mineralogical analyses were also conducted on a selection of the ceramic sherds using X-ray diffraction (XRD) as well as paste and petrographic analyses. The results of this study correspond with prior research (Bland et al., 2017a) which concluded that the majority of domestic ceramics from the Caleta Vitor Archaeological Complex were manufactured using local resources. Here, we expand this discussion by identifying four ceramic paste groups that would constitute local pottery traditions of manufacture. The identified paste groups are relatively consistent and span almost all time periods examined (Formative c. 4000–1500 BP through to Hispanic c. 467 BP Periods). These results support the argument that these ceramic traditions were maintained by the coastal communities of Caleta Vitor, despite the fact that they were integrated into interregional networks of interactions through time, including their relationships with powerful Andean polities. These apparent continuities in domestic ceramic production allow us to reflect on local decision-making processes throughout relevant cultural phases, and to conclude that foreign pottery did not have an exchange value.